COEXISTENCE OF RENAL CELL CARCINOMA AND HEMATOLOGICAL MALIGNANCIES - Gokhan Sargin; Irfan Yavasoglu; Gurhan Kadikoylu; Firuzan Kacar Doger; Zahit Bolaman (Mediterranean Journal of Hematology and Infectious Diseases, 2014)
Renal cell carcinoma (RCC) and multiple myeloma (MM) accounts for 1-3% of adult malignancies and secondary primary tumors accounts for 5-8% of all malignant cases. Hematologic malignancies are rarely observed with RCC. The relationship between solid tumors and lymphoid neoplasms may be due to chemotherapy or radiation therapy.